Social-economic profile of asthmatic patients assisted at a Nucleus of Integrated Medical Assistance - doi:10.5020/18061230.2008.p180 - Anisia Torquilho Praxedes; Ismael Leite Martins; Lígia Vieira Uchoa; Vânia Cordeiro de Matos (Universidade de Fortaleza, 2012)
Objective: To determine the social-economic profile of asthmatic patients who use the health services rendered by the Nucleus of Integrated Medical Assistance (NAMI), in Fortaleza- Ce. Methods: This descriptive, retrospective and cross-sectional study, of a quantitative approach, had a sample comprised by 40 asthmatic patients assisted at NAMI during the period of April to May, 2006. The data collection was accomplished by means of a standard semi-structured interview, with open and closed questions. Results: The age range between 0 to 5 years old represented the greater percentage of patients, thus obtaining 60.0% of the answered questionnaires. According to social-economic conditions, 55.0% were illiterate or were learning to read, 75.0% were using some drug prescribed at NAMI, 72.5% fully ignored the disease, 52.5% recognized the factors that triggered the asthmatic crisis and 55.0% said having often crisis. Seventy per cent (70.0%) of the interviewed showed some difficulty related to the use of the drugs; 47.5% referred having different problems related to the access to the medications. Conclusion: By the analysis of the determined social-economic profile of asthmatics patients assisted at NAMI, it is concluded that great part of them are people with little instruction, due to the social exclusion in which they are found; being the majority of them children of female gender. NCT00722657